Event based control of propofol and remifentanil coadministration during clinical anesthesia - Merigo, L.; Beschi, M.; Padula, Fabrizio; Latronico, N.; Paltenghi, M.; Visioli, A. (2017)
© 2017 IEEE. In this paper we present an event-based methodology for the control of the depth of hypnosis in general anesthesia. The control system is based on the implementation of an event generator with strong noise filtering capabilities together with a PIDPlus controller and considers both the administration of propofol and remifentanil in order to obtained a desired level of the bispectral index scale. Simulation results obtained with a wide set of patients model demonstrate the effectiveness of the method in both the induction and maintenance phases and how the technique can be appreciated in practical cases as it mimics the behaviour of the anesthesiologist.